24. Wykonaj dzialania:
a) a + (a - b)
b) 2x - (x + 4)
c) 7 - (-x + 6)
d) -(x + 4) + (x -5)
e) 1 - (t + p) - (t - 2)
f) -(-y + 2) + (-2y - 4)

25. Zapisz w jak najprostszej postaci.
a) (a + b) - (2a -b) - (a - 2b)
b) (3x - y + 1) - (x + y) - (y - x)
c) - (kx + ny) - (3kx + 2ny) + (5kx - 3 ny)
d) (2ab + a + 3) - (3ab - a + 3)
e) (4x2 - 3x) - (x + 0,1x2) - (x2 - 0,1x)


DZIEKUJE JESLI KTOS ROZWIAZE. PROSILBYM O PELNE DZIALANIA!.

2

Odpowiedzi

2010-02-18T21:40:18+01:00
24. Wykonaj dzialania:
a) a + (a - b) = a+a-b=2a+b
b) 2x - (x + 4) = 2x-x-4=x-4
c) 7 - (-x + 6) = 7 + x-6 = 1+x
d) -(x + 4) + (x -5) = -x-4+x-5=2x-9
e) 1 - (t + p) - (t - 2) = 1-t-p-t+2= 3-2t-p
f) -(-y + 2) + (-2y - 4) = y-2-2y-4 = -y-6

25. Zapisz w jak najprostszej postaci.
a) (a + b) - (2a -b) - (a - 2b) = a+b-2a+b-a+2b = -2a+4b
b) (3x - y + 1) - (x + y) - (y - x) = 3x-y+1 - x-y-y+x = 3x-3y+1
c) - (kx + ny) - (3kx + 2ny) + (5kx - 3 ny) = -kx-ny-3kx-2ny+5kx-3ny = kx-6ny
d) (2ab + a + 3) - (3ab - a + 3) = 2ab+a+3-3ab+a-3 = -ab+2a
e) (4x² - 3x) - (x + 0,1x²) - (x² - 0,1x) = 4x²-3x-x-0,1x²-x²+0,1x = 2,9x²-3,9x
4 5 4
2010-02-18T23:29:35+01:00

zad.24
a)a+a-b=2a+b
b)2x-x-4=x-4
c)7 + x-6 = 1+x
d)-x-4+x-5=2x-9
e)-x-4+x-5=2x-9
f)y-2-2y-4 = -y-6


zad.25
a)a+b-2a+b-a+2b = -2a+4b
b)3x-y+1 - x-y-y+x = 3x-3y+1
c)-kx-ny-3kx-2ny+5kx-3ny = kx-6ny
d)2ab+a+3-3ab+a-3 = -ab+2a
e)4x²-3x-x-0,1x²-x²+0,1x = 2,9x²-3,9x
1 5 1